The Influence of Information Center Management, Early Marriage Knowledge, and Reproductive Health Counseling on Stunting Prevention Understanding - Megawati; Yunus Handoko; Ike Kusdyah Rachmawati (Al-Qalam Institue, 2026)
This study aims to analyze the influence of Information Center Management, Early Marriage Knowledge, and Reproductive Health Counseling on adolescents’ understanding of stunting prevention. Limited utilization of youth information and counseling services, low awareness of early marriage risks, and suboptimal reproductive health counseling reduce adolescents’ preventive knowledge regarding stunting. A quantitative approach with an associative design was applied. The population consisted of high school students, with a sample selected using random sampling. Data were collected through structured questionnaires that had been tested for validity and reliability. Analyses included instrument testing, classical assumption tests, multiple linear regression, F-test for simultaneous effects, and t-test for partial effects. The results indicate that Information Center Management and Early Marriage Knowledge significantly affect adolescents’ understanding of stunting prevention, while Reproductive Health Counseling shows a positive but not statistically significant effect. These findings emphasize the importance of well-managed information services and comprehensive knowledge dissemination in enhancing adolescents’ awareness and preventive behaviors. The study provides practical insights for integrating educational management, reproductive health education, and early marriage awareness into programs aimed at strengthening stunting prevention among adolescents.